A comprehensive assessment of four whole blood stabilizers for flow‐cytometric analysis of leukocyte populations. Issue 4 (1st November 2022) - Nguyen, Ngoc Anh; Huang, Xiaobo; Cabrera, Luz E.; Pekkarinen, Pirkka T.; Nowlan, Kirsten; Strandin, Tomas; Kantele, Anu; Vapalahti, Olli; Heinonen, Santtu; Kekäläinen, Eliisa
Abstract: Though cryopreservation of cell fractions is widely used in flow cytometry studies, whole blood cryopreservation is more challenging due to the presence of erythrocytes and effects of fixatives commonly used for preservation. Here, we evaluated and compared head‐to‐head the performance of four commercial whole blood cryopreservation kits; (1) Cytodelics, (2) Stable‐Lyse V2 and Stable‐Store V2 (SLSS‐V2), (3) Proteomic stabilizer (PROT‐1), and (4) Transfix. We found that PROT‐1, Transfix, and Cytodelics maintained the distribution of major leukocyte subsets—granulocytes, T cells, natural killer cells, and B cells, on a comparable level to unpreserved samples, despite the attenuation of fluorescence intensities in flow cytometric assays. Moreover, these three stabilizers also maintained the activated phenotypes of neutrophils upon stimulation with N ‐formylmethionyl‐leucyl‐phenylalanine and lipopolysaccharides. The upregulation of adhesion molecules (CD11b), Fc receptors (CD16), and granule proteins (CD66b), as well as the shedding of surface L‐selectin (CD62L), was conserved most efficiently in PROT‐1 and Cytodelics when compared to samples only treated with erythrocyte lysing. However, none of the stabilizers provided a reliable detection of CCR7 for accurate quantification of T cell maturation stages. We also evaluated the performance of Cytodelics in longitudinal clinical samples obtained from acute COVID‐19 patients, where it allowed reliable detection of lymphopenia and granulocyte expansion. These results support the feasibility of whole blood cryopreservation for immunophenotyping by flow cytometry, particularly in longitudinal studies. In conclusion, the performance of different stabilizers is variable and therefore the choice of stabilizers should depend on cell type of interest, as well as antibody clones and experimental design of each study.